Single dose regorafenib-induced hypertensive crisis - Yilmaz, B.; Kemal, Y.; Teker, F.; Kut, E.; Demirag, G.; Yucel, I. (Experimental Oncology, 2014)
Gastrointestinal stromal tumors (GISTs) are uncommon tumors of the gastrointestinal (GI) tract. Regorafenib is a new multikinase inhibitor and is approved for the treatment of GISTs in patients who develop resistance to imatinib and sunitinib. The most common drug-related adverse events with regorafenib are hypertension, hand-foot skin reactions, and diarrhea. Grade IV hypertensive side effect has never been reported after a single dose. In this report, we present a case of Grade IV hypertensive side effect (hypertensive crisis and seizure) after a single dose of regorafenib. A 54-year-old male normotensive GIST patient was admitted to the emergency department with seizure and encephalopathy after the first dosage of regorafenib. His blood pressure was 240/140 mmHg upon admission. After intensive treatment with nitrate and nitroprusside, his blood pressure returned to normal levels in five days. Regorafenib was discontinued, and he did not experience hypertension again. This paper reports the first case of Grade IV hypertension after the first dosage of regorafenib. We can suggest that hypertension is an idiosyncratic side effect unrelated to the dosage. Key Words: hypertension, regorafenib, gastrointestinal stromal tumor.